The molecular biology of matrix metalloproteinases and tissue inhibitors of metalloproteinases in inflammatory bowel diseases. (2nd September 2016) - de Bruyn, Magali; Vandooren, Jennifer; Ugarte-Berzal, Estefania; Arijs, Ingrid; Vermeire, Séverine; Opdenakker, Ghislain
Abstract: Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) are thought to be predominant proteases and protease inhibitors involved in the pathogenesis of inflammatory bowel diseases (IBD) through their ability to remodel the extracellular matrix (ECM) in response to inflammatory stimuli and by their immunomodulating effects. An imbalance between MMPs and TIMPs has been linked with acute and chronic inflammation and aberrant tissue remodeling, as seen in IBD. Moreover, recurrent phases of tissue destruction and subsequent tissue repair can cause serious complications in IBD patients such as fistulas and fibrosis. The aims of this review are (i) to summarize current literature on genetic association, mRNA, and protein expression studies with regard to MMPs and TIMPs in IBD patients and various animal models, including those with transgenic and knockout mice; (ii) to compare biochemical and molecular biological data in humans with those obtained in animal model studies and (iii) to critically evaluate and translate how this knowledge may be used in practical terms to understand better the pathophysiology and mechanisms operating in IBD and to apply this for improvement of clinical outcomes at diagnostic, prognostic and therapeutic levels.